A Comparison of Topical or Retrobulbar Anesthesia for 23-Gauge Posterior Vitrectomy - ÇELİKER ATABERK, HANDE; ŞAHİN, ÖZLEM (HINDAWI LTD, 2014)
Background. To compare the efficacy and safety of topical anesthesia versus retrobulbar anesthesia in 23-gauge vitreoretinal surgery. Materials and Methods. A total of 63 patients scheduled for 23G posterior vitrectomy without scleral buckling procedures were included in the study. The patients were randomly assigned to receive either topical (Group 1, n = 31) or retrobulbar anesthesia (Group 2, n = 32). Postoperatively, patients were shown a visual analogue pain scale (VAPS) from 1 (no pain or discomfort) to 4 (severe pain or discomfort) to rate the levels of pain. Results. There was more discomfort in patients in Group 2 while anesthetic was administered (Group 1: 1.0 +/- 0, Group 2: 2.3 +/- 0.7, n = 0.0001). Between the two groups the level of pain during surgery (Group 1: 1.4 +/- 0.5, Group 2: 1.5 +/- 0.5; n = 0.85) was noted. There was also no significant difference between two groups postoperatively (Group 1: 1.2 +/- 0.4, Group 2: 1.3 +/- 0.4; n = 0.28). There were no complications in either group related to the anesthetic technique. No patient needed sedation or anesthesia supplement during the surgery or postoperative period. Conclusion. Topical anesthesia in posterior vitrectomy procedures is an effective and safe method that is alternative to retrobulbar anesthesia.
Keywords: INTRAOCULAR-LENS IMPLANTATION; PERIBULBAR ANESTHESIA; GLOBE PERFORATION; OPTIC-NERVE; PHACOEMULSIFICATION; INJECTION